2015
DOI: 10.1902/jop.2015.140666
|View full text |Cite
|
Sign up to set email alerts
|

Level of Interleukin‐35 in Gingival Crevicular Fluid, Saliva, and Plasma in Periodontal Disease and Health

Abstract: IL-35 could have an important role in suppressing periodontal inflammation and maintaining periodontal health. Additional studies are required to evaluate its role in periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
0
27
1
1
Order By: Relevance
“…145 More recently, there has been a further attempt to characterize the GCF profile of a patient with gingivitis (i.e., a patient with a ( Table 3). [146][147][148][149][150][151][152][153][154][155] Overall, these studies indicate that the GCF proteomic profile of gingivitis subjects is qualitatively and quantitatively different from that of periodontal health; more specifically, a greater number of proteins have been found in gingivitis compared to periodontal health. 153 Moreover, the amount of some proteins (e.g., IL-1b, ALP, complement factors, MMP-9, fibronectin, lactotransferrin precursors, alpha-actinin) is higher in gingivitis compared to periodontal health, 147,153 while other proteins (e.g., cystatin-B, cystatin-S) are present in lower amounts in gingivitis.…”
Section: Gcf Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…145 More recently, there has been a further attempt to characterize the GCF profile of a patient with gingivitis (i.e., a patient with a ( Table 3). [146][147][148][149][150][151][152][153][154][155] Overall, these studies indicate that the GCF proteomic profile of gingivitis subjects is qualitatively and quantitatively different from that of periodontal health; more specifically, a greater number of proteins have been found in gingivitis compared to periodontal health. 153 Moreover, the amount of some proteins (e.g., IL-1b, ALP, complement factors, MMP-9, fibronectin, lactotransferrin precursors, alpha-actinin) is higher in gingivitis compared to periodontal health, 147,153 while other proteins (e.g., cystatin-B, cystatin-S) are present in lower amounts in gingivitis.…”
Section: Gcf Proteomicsmentioning
confidence: 99%
“…143 Some studies have characterized the salivary proteomic profile of gingivitis (i.e., a patient with a given amount of gingival inflammation and no attachment/bone loss) compared to periodontal health (Table 4). 146,154,155,[157][158][159][160] The analyses showed that gingivitis was associated with significantly increased amounts of blood proteins (serum albumin and hemoglobin), immunoglobulin peptides and keratins, 158 PGE2 and MIP-1α, 160 and more than double the amounts of MMP-8, MMP-9, and IL-6. 157 In periodontal health, salivary cystatins appeared to be more abundant.…”
Section: Salivary Proteomicsmentioning
confidence: 99%
“…The results in our study are comparable to the study by Koseglu. 7 In this study, the mean GCF However, the results might alter due to changes in the concentration of other anti-inflammatory cytokines, which cannot be denied. This is one of the important limitations of this study.…”
Section: Discussionmentioning
confidence: 66%
“…As of now only one study has compared the levels of IL-35 in plasma, saliva, and gingival crevicular fluid (GCF) in periodontal health and disease. 7 In our previous study,…”
mentioning
confidence: 89%
“…Tooth position, incorrect tooth brushing techniques, and chemical or mechanical trauma are among these etiological factors. (1) Biological width which is composed by epithelial attachment and subjacent connective tissue is considered as an adaptation mechanism of the body occurring where epithelial tissue is perforated by teeth and GR may arise from its violation by various dental restorations. (2) GR causes cervical dentin hypersensitivity, pain, and difficulty while toothbrushing.…”
Section: Introductionmentioning
confidence: 99%